Futures thinking in market-shaping research: Developing an onto-epistemological foundation and analytical framework - Halinen, Aino; Kaartemo, Valtteri; Tapio, Petri (Elsevier, 2026)
Although market‑shaping research is inherently future‑oriented, it has paid limited attention to how actors envision future markets. Companies’ visions are assumed to drive market‑shaping efforts, yet how these visions are constructed and evolve remains underexplored. Two fundamental weaknesses account for this omission. First, the ontological and epistemological assumptions of market-shaping research are inconsistent. Second, the mental models that market-shaping actors form about future markets have largely been neglected. To address these shortcomings, this study proposes systematic incorporation of futures thinking into market-shaping research. Drawing on futures research, it develops an onto‑epistemological foundation for future-oriented market-shaping studies and introduces an analytical framework for examining actors’ mental models of how markets could or should be developed. The paper concludes with a research agenda encouraging empirical inquiry into how market actors anticipate and respond to uncertainties and cultivate alternative views beyond singular, deterministic visions.